Building Healthcare Brand: Role of service, image, and trust - Pradeep Kumar; Shashank Mittal; Shubham Kumar (ACHSM, 2024)
Objective: Healthcare branding is a recent concept, and its theoretical modeling is still somewhat inadequate. This paper examines how perceived service quality affects healthcare brand performance, brand image, and behavioral intention. Methods: The present study uses survey responses from 678 patients who have taken treatment in multi-specialty medical institutes. Standard scales were used from the literature to measure the variables used. The conceptual model was validated using structural equation modeling using AMOS. SPSS was used to determine the validity and reliability of the questionnaire. Results: The theoretical model has a relatively high and significant coefficient path for each of the hypotheses. The R2 value for satisfaction was 0.70 or 70 percent. The R2 value for the trust was 0.78. For Brand performance, Brand image and behavioral intentions were 81, 82.5, and 74%, respectively. Overall, the scores suggest an acceptable level of measure score and predictive ability of the relevant constructs. The results disclose the dimensions of service quality in the circumstances of healthcare. The patients place relatively more importance on healthcare service quality than any other attributes of healthcare institutions. Service quality has a high beta value of 0.98 and p p-value of 0.000. Conclusion: The study makes an innovative theoretical contribution by establishing a relationship between experience-centric healthcare brand performance and brand image. Patient satisfaction and trust were demonstrated to mediate the relationship between perceived service quality, brand performance, brand image, and behavioral intention in a healthcare context. The study established the novel finding that trust and satisfaction play a significant role in service quality, brand performance, and brand image of healthcare institutions. This study also shows that brand performance has a positive and significant direct effect on brand performance. This shows the dependency of brand image on brand performance in the healthcare institution context.